N2 fixation as a dominant new N source in the western tropical South Pacific Ocean (OUTPACE cruise) - M. Caffin; T. Moutin; R. A. Foster; P. Bouruet-Aubertot; A. M. Doglioli; H. Berthelot; H. Berthelot; C. Guieu; C. Guieu; O. Grosso; S. Helias-Nunige; N. Leblond; et al. (Biogeosciences, 2018)
We performed nitrogen (N) budgets in the photic layer of three contrasting stations representing different trophic conditions in the western tropical South Pacific (WTSP) Ocean during austral summer conditions (February–March 2015). Using a Lagrangian strategy, we sampled the same water mass for the entire duration of each long-duration (5 days) station, allowing us to consider only vertical exchanges for the budgets. We quantified all major vertical N fluxes both entering (N2 fixation, nitrate turbulent diffusion, atmospheric deposition) and leaving the photic layer (particulate N export). The three stations were characterized by a strong nitracline and contrasted deep chlorophyll maximum depths, which were lower in the oligotrophic Melanesian archipelago (MA, stations LD A and LD B) than in the ultra-oligotrophic waters of the South Pacific Gyre (SPG, station LD C). N2 fixation rates were extremely high at both LD A (593 ± 51 µmol N m−2 d−1) and LD B (706 ± 302 µmol N m−2 d−1), and the diazotroph community was dominated by Trichodesmium. N2 fixation rates were lower (59 ± 16 µmol N m−2 d−1) at LD C, and the diazotroph community was dominated by unicellular N2-fixing cyanobacteria (UCYN). At all stations, N2 fixation was the major source of new N (> 90 %) before atmospheric deposition and upward nitrate fluxes induced by turbulence. N2 fixation contributed circa 13–18 % of primary production in the MA region and 3 % in the SPG water and sustained nearly all new primary production at all stations. The e ratio (e ratio  =  particulate carbon export ∕ primary production) was maximum at LD A (9.7 %) and was higher than the e ratio in most studied oligotrophic regions (< 5 %), indicating a high efficiency of the WTSP to export carbon relative to primary production. The direct export of diazotrophs assessed by qPCR of the nifH gene in sediment traps represented up to 30.6 % of the PC export at LD A, while their contribution was 5 and < 0.1 % at LD B and LD C, respectively. At the three studied stations, the sum of all N input to the photic layer exceeded the N output through organic matter export. This disequilibrium leading to N accumulation in the upper layer appears as a characteristic of the WTSP during the summer season.